Designing and Prototyping of a Battery Management System for Solar Power Plants in Uganda. - Ssembalirwa, Denis (Kabale University, 2024)
In Uganda, the efficiency and reliability of solar power plants are often compromised due to inadequate battery management, leading to suboptimal performance and reduced battery lifespan. This project addresses this critical issue by designing and prototyping a Battery Management System (BMS) specifically for solar power plants. The proposed BMS monitors essential battery pack parameters such as voltage, load current, and temperature. Utilizing IoT technology, it transmits real-time data to the cloud, enabling global monitoring of the battery’s state. Additionally, the system employs intelligent algorithms to autonomously manage the charging and discharging cycles based on the battery’s condition. This innovative solution aims to enhance the reliability and efficiency of solar power systems, thereby promoting sustainable energy development in Uganda.